A conceptual framework of the impact of maternal early life drought exposure on newborn size in Malawi. Issue 1 (1st January 2021) - Hanjahanja-Phiri, Thokozani
Abstract: The effects of adverse prenatal conditions are not only experienced over the life course but can be passed on intergenerationally. The present study took advantage of a natural experiment from three drought periods of 1981/82, 1987/88, and 1992/93 that occurred in Malawi with varying severity and used data from a randomized clinical trial (RCT), conducted between 2011–2015 (Protocol #NCT01239693). The present study aimed to assess the effect of the interactions between maternal exposure to drought in early life and prenatal supplementation with a novel supplement [small quantity (SQ), lipid-based nutrient supplement (LNS)], the standard of care prenatal supplement [iron-folic acid or IFA], or a close substitute of the standard of care [multiple micronutrients or MMN], on subsequent infant birth outcomes. During data analysis, ordinary least squares were used to run multiple regressions. The regression results were as follows. When there was no maternal exposure to drought, SQ-LNS compared to IFA appeared to improve subsequent infant birth outcomes for length-for-age Z score or LAZ (0.403 standard deviation (SD), Confidence interval CI [0.099, 0.708]), for subsequent infant weight-for-age Z score or WAZ (0.372 SD, CI [0.053, 0.691]), and for imputed infant birthweight or BTW (125.900 g, CI [2.901, 248.899]). In conclusion, the results show a pattern emerging whereby some positive associations can be observed, specifically, when maternal non-drought exposure variables and the SQ-LNS variable interact. Their combined effects on subsequent infant birth outcomes notably subsequent infant LAZ, subsequent infant WAZ, and subsequent infant imputed BWT appear to be positive.